Consumption and Capital Market Imperfections: An International Comparison - Jappelli, Tullio; Pagano, Marco (American Economic Review, 1989)
The excess sensitivity of consumption to current income fluctuations is higher in countries where consumers borrow less. Low levels of consumer debt can result either from capital market imperfections or from a low demand for loans. The evidence suggests that the former view is more appropriate than the latter, and thus supports the hypothesis that excess sensitivity may be attributed to liquidity constraints, rather than to other factors.